2016
DOI: 10.1007/s00158-016-1515-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of direct inverse maps to solve material identification problems: pitfalls and solutions

Abstract: Material parameter identification is a technique that is used to calibrate material models, often a precursor to perform an industrial analysis. Conventional material parameter identification methods estimate the material parameters for a material model by solving an optimisation problem. An alternative but lesser-known approach, called a direct inverse map, directly maps the measured response to the parameters of a material model. In this study we investigate the potential pitfalls of the well-known stochasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The liquid compositions were determined by an inverse mapping approach. A surrogate model of the inverse system was constructed to map the measured system response to the system parameters directly 23 . Partial least squares regression (PLSR) was used to construct the inverse map 15 , 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The liquid compositions were determined by an inverse mapping approach. A surrogate model of the inverse system was constructed to map the measured system response to the system parameters directly 23 . Partial least squares regression (PLSR) was used to construct the inverse map 15 , 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Experiment can be tightly controlled and therefore there is no uncertainty in whether or not the inverse method finds the true answer (Wilke et al, 2010;Asaadi et al, 2017;Ben Turkia et al, 2019). One first generates a virtual experiment for a given loading condition which returns stresses, strains, deformations, and forces.…”
Section: Virtual Experimentsmentioning
confidence: 99%
“…Rahmani et al identified the constituent mechanical properties with an improved regularized model updating (RMU), which reduces the influence of measured noise simultaneously [22]. Other methods such as the Kalman filter, regularized virtual fields Levenberg-Marquardt, and direct inverse maps [42] were proposed to identify parameters of composite material. Images were also used to predict the mechanical properties of materials [43].…”
Section: Introductionmentioning
confidence: 99%